HUBUNGAN INSIDEN FISTULA URETROKUTANEUS DENGAN TIPE HIPOSPADIA PASCA OPERASI URETROPLASTI - Wendy Desrullah Prada; Tubagus Odih Rhomdani Wahid; Laode Burhanuddin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Hypospadias is the second most common congenital abnormalities of thepenis. Management of hypospadias performed with a surgical procedure that iscordectomy and urethroplasty. Urethrokutaneus fistula is the most common posturethroplasty surgery complications in patients with hypospadias. This study is aretrospective analytic correlative with cross sectional approach conducted inDecember 2014 - January 2015. Retrieved 61 medical records of patientshypospadias in surgery section of Arifin Achmad Riau Province period January2011 - December 2013. From this study, the incidence of hypospadias by types:anterior 21.31%, medial 34.42%, and posterior 29.50%. Type hypospadias isoften become urethrocutaneus fistula post urethroplasty surgery is posteriorhypospadias type (72.2%), hypospadias type medius (19.0%), anteriorhypospadias type 18.2%. Results of Chi-Square test of correlation between theincidence of hypospadias fistula with the type of post uretroplasty obtained fromthe chi-square value is 16.162 and p-value <0.0001. Conclusion the study is asignificant differences in incidence urethrokutaneus fistula with type ofhypospadias post urethroplasty surgery.Key words : hypospadias, type of hypospadias, urethrocutaneous fistula,urethroplasty